The Cluster Transfer Function of AtNEET Supports the Ferredoxin-Thioredoxin Network of Plant Cells - Sara I. Zandalinas; Luhua Song; Rachel Nechushtai; David G. Mendoza-Cozatl; Ron Mittler (MDPI AG, 2022)
NEET proteins are conserved 2Fe-2S proteins that regulate the levels of iron and reactive oxygen species in plant and mammalian cells. Previous studies of seedlings with constitutive expression of AtNEET, or its dominant-negative variant H89C (impaired in 2Fe-2S cluster transfer), revealed that disrupting AtNEET function causes oxidative stress, chloroplast iron overload, activation of iron-deficiency responses, and cell death. Because disrupting AtNEET function is deleterious to plants, we developed an inducible expression system to study AtNEET function in mature plants using a time-course proteomics approach. Here, we report that the suppression of AtNEET cluster transfer function results in drastic changes in the expression of different members of the ferredoxin (Fd), Fd-thioredoxin (TRX) reductase (FTR), and TRX network of Arabidopsis, as well as in cytosolic cluster assembly proteins. In addition, the expression of Yellow Stripe-Like 6 (YSL6), involved in iron export from chloroplasts was elevated. Taken together, our findings reveal new roles for AtNEET in supporting the Fd-TFR-TRX network of plants, iron mobilization from the chloroplast, and cytosolic 2Fe-2S cluster assembly. In addition, we show that the AtNEET function is linked to the expression of glutathione peroxidases (GPXs), which play a key role in the regulation of ferroptosis and redox balance in different organisms.